MEREAFaPS: uno Studio di Farmacovigilanza Attiva e Farmacoepidemiologia in Pronto Soccorso - Lombardi, Niccolò (Premio Tesi di Dottorato, 2016)
Adverse drug reactions (ADRs) have a significant impact on the patient's health. The purpose of this PhD thesis was to analyse the impact of ADRs on the admissions to the emergency room, using the data obtained from the MEREAFaPS study. Elderly patients resulted the most exposed group to ADRs. Gastrointestinal disorders were the most commonly reported adverse reactions. Acetylsalicylic acid and warfarin were the most reported drugs. 17% of serious ADRs and 32% of the resulting deaths were classified as avoidable. Elderly age was found to be the main risk factor associated with ADRs. It is therefore important to underline the need for a more careful use of drugs in this group of patients.